"I am Responsible" Campaign. - Ho, Serene Mei Lin. (2009)
The number of new HIV cases has been on the increase each year. Contrary to popular belief that homosexuals are the ones that are most prone to getting AIDS, research has shown that the most common mode of transmission is actually through heterosexual sex. This year-long campaign titled “I am Responsible” was targeted at heterosexual males from the age of 27 and above with the tendency to (a) visit KTV pubs frequently, (b) visit the Riau-Islands frequently for commercial sex. Through a series of activities, that include a campaign launch and a Getai, three objectives were hoped to be obtained. 1. For males to wear a condom during sex; 2. For males to go for regular HIV testing; 3. For males to have the thinking of “I am Responsible”; That they are responsible for not only their own lives, but also of their loved ones. Through pre and post event surveys conducted, the findings reveal that while many of the respondents have a general knowledge of HIV/AIDS, they do not go for regular screening as they are lulled into the thinking that they are not at risk. Many also are not sure of where are the places they can go for anonymous testing. However after the events, many of the respondents said that not only would they use a condom during sex; they would also go for regular HIV screenings.